The Impact of Digital Transformation on Improving Human Resource Management Performance: The Mediating Role of Strategic Decision Quality – an Analytical Study in the Ministry of Education / Al-Karkh II Directorate - Ali Abdul Salam Abdul Daim (Research Parks Publishers, 2026)
In this research, an effort will be made to investigate the impact of digital transformation on the performance of human resource management (HRM) performance, through the mediation of the quality of strategic decision making in the Ministry of Education, the Directorate of Al-Karkh II. Digital Transformation is assumed as an independent variable, whose dimensions include digital skills, digital technology adoption and digital working environment. Strategic decision quality acts as the mediator, which has dimensions such as decision relevance, decision acceptance and decision quality. The dependent variable in the research is HRM performance, which includes dimensions of task performance, administrative performance and capability performance. The descriptive analytical approach was used in this study. For data collection, questionnaires were distributed among the random samples of 286 employees and administrative executives of the Directorate of the Second Karkh. Data were analyzed using SPSS v26 and AMOS v24 software and through using appropriate statistical tools such as multiple linear regression and structural equation modeling. From the findings, it is clear that there is a significant positive influence of digital transformation on HRM performance and significant influence of digital transformation on strategic decision quality. Moreover, there is significant influence of strategic decision quality on HRM performance. It has been found that there is partial mediation of strategic decision quality in the relationship between digital transformation and HRM performance. Therefore, the importance of using digital technologies in the process of administrative and strategic decision to improve the performance of organization should be noted. Based on the findings of the study, some recommendations can be given to increase the effectiveness of digital transformation initiatives, develop employees' digital skills, provide integrated digital working environment and use modern digital technologies to support the quality of strategic decisions.